MANIFESTASI KLINIS DAN PROFIL HEMATOLOGI BALITA DENGAN DIARE AKUT DI RSD IDAMAN BANJARBARU TAHUN 2020-2021 - Gita Shabella; Harapan Parlindungan Ringoringo; Meitria Syahadatina Noor (Homeostasis, 2022)
Acute diarrhea is an increase in stool discharge with a softer or more liquid consistency than usual, occurring at least 3 times in 24 hours with or without mucus and blood lasting <14 days. The purpose of this study is to find out the clinical manifestations, hematology profile, and examination of feces of children under five at Idaman Banjarbaru Hospital in 2020-2021. The methods used in this study are descriptive retrospective. Data retrieval techniques are done purposive sampling by paying attention to inclusion and exclusion criteria. The study sample included 35 children with clinical manifestation data and a complete hematological profile. The results showed the most age in the group of 12-36 months with a percentage of 60%. By gender there were 21 children (64.86%) male. The study concluded that 27 children (77.14%), were in vomiting in 26 children (74.28%). The majority with normal leukocyte levels with a percentage of 22 (62.85%) children, hemoglobin levels within normal limits are as many as 25 children (71.43%).